Konsumsi Oksigen, Kadar Hb Darah, Dan Pertumbuhan Ikan Mas, Cyprinus carpio, Diberi Pakan Campuran Ampas Kelapa - Darmadi Goenarso; Suripto Suripto; K I Susanthi (Institut Teknologi Bandung, 2003)
A laboratory experiment on carp (Cyprinus carpio) given a shredded coconut mixed diet has been conducted. Carp aged 4 â 5 months (n = 50; weight = 24,46-25,78 g), were kept individually in each aquarium (50x30x30 cm). The waste shredded coconut was mixed with commercial fish feed. Five concentrations (w/w) of mixed diet were given as treatment, i.e.: 30% (P30), 40% (P40), 50% (P50), and 60% (P60). Controlled fish was only given commercial feed. The experiment was done within 10 weeks with five replicates. Fish were fed twice daily as much as 10% of body weight. Measurements on oxygen consumption rate and body weight were done weekly. The fish were kept from food for 24 hours prior to measurements. The hemoglobin concentration was measured at the beginning and at the end of the experiment only. ANOVA was used for statistical tests. Results showed that the oxygen consumption rate of the treated fish was not different from the controlled fish. Relative growth rate decreased significantly. The average growth rate of fish treated with P30, P40, P50, P60, were respectively 0.042%, 0.041%, 0.031% and 0.018%. Growth rate of controlled fish was 0.104%. There was n o difference on the hemoglobin concentration measured at the end of the experiment (7.89 mg/dl) compared to the value at the start (7.91 mg/dl) of the experiment. It can be concluded that waste shredded coconut mixed diet might be used as fish feed. However, some improvements should be done on the composition of nutrition in the diet to increase the fish growth rate.